Single and two-component grout as high-performance backfilling materials - Di Giulio, A.; Di Felice, M.; Valiante, N.; De Carli, G. (Expanding Underground - Knowledge and Passion to Make a Positive Impact on the World, 2023)
Segmental lining is not usually applied in hydraulic pressure tunnels but may become a viable alternative if it can withstand internal pressure variations and it is possible to fill the tunnel annular gap with high-performance backfilling material, as single-component grout or pea gravel. The research here presented is aimed at studying a mix design for the backfill to be used in a pressure tunnel subjected to severe hydraulic conditions, considering both single and two-component grout. The requirements (high strength and stiffness, cyclic load resistance and durability) are quite common when considering a traditional grout but become challenging for a two-component one. The experimentation consisted in a preliminary phase to find mix designs that conjugated pumpability of the fresh mixture and mechanical properties of the hardened grout, followed by a testing phase on the best recipes, under static and cyclic loads. This paper presents a comparison between the two solutions.